SOCIALIZATION AND APPLICATION OF THE FLIPPED CLASSROOM LEARNING METHOD IN THE NURSING METHODOLOGY COURSE FOR NURSING STUDENTS OF THE JAYAPURA MINISTRY OF HEALTH POLYTECHNIC - Kusuma, Ardhanari H.; Arisjulyanto, Dedy; Mulyono, Sri (Pusat Riset dan Inovasi Nasional, 2022)
Background: The current conditions are challenging to demand students to play an active role, get high marks, and have good nursing competence. It happens because the learning method is not exactly applied to increasing the interaction of students and lecturers in the classroom. Laboratory practicum is monotonous and carried out in a brief time also affects it. In addition, the lack of learning media makes student learning motivation very low. It has an impact on student passivity. They also do not understand the importance of learning and developing nursing competencies to become professional and dignified nurses. Method: The research design uses a Quasi Experiment. It is a research design with a purposive sampling technique. The purpose of this study was to find out the difference in the level of student knowledge before and after the application of the flipped classroom learning method. It conducted twice observations. They are before and after being given the flipped classroom learning method. The student's knowledge level was measured twice, namely before the flipped classroom learning method was applied (pre-test) and after the flipped classroom learning method was applied (Posttest). The sample in the study was 41 respondents. The research data were analyzed using the Paired T-Test with a significant traffic P value <α=0.05. Result: The results of the research on the application of the Flipped classroom learning method obtained a mean value of student knowledge of 35.36. There was an increase of 51.95 to 87.31, with a p-value of 0.000 <α=0.05. Conclusion: There is an influence of the application of the Flipped Classroom learning method on the level of knowledge of Nursing Students at Health Polytechnic Jayapura. In this research, the researchers hoped that it can be used as an evaluation material and become an effective learning method to increase students' knowledge and learning motivation at the Jayapura Ministry of Health Polytechnic.